T-gate with dual dielectric layer for p-GaN/AlGaN/GaN HFETs: Suppressed gate leakage current and increased gate voltage range - Min-Gi Jeong; Gökhan Atmaca; Ho-Young Cha (Results in Physics)
In this paper, a T-shaped gate with a dual dielectric layer is proposed for enhancement-mode p-GaN/AlGaN/GaN heterojunction field-effect transistors (HFETs), designed to reduce gate leakage current and improve gate forward breakdown voltage. The proposed dual dielectric layer, comprising Al2O3 and SiO2 films, modulates the energy band structure at the gate edge to suppress the hole injection from the gate metal to the p-GaN layer. As a result, the p-GaN/AlGaN/GaN HFET with the proposed T-shaped gate demonstrated a significantly reduced gate leakage current of ∼ 10-7 A/mm at VGS = 8 V and a substantially higher gate forward breakdown voltage of 16 V, compared to a conventional structure with a gate leakage current of ∼ 10-3 A/mm at VGS = 8 V and a gate forward breakdown voltage of 8.5 V. Additionally, the off-state breakdown voltage of the proposed device was noticeably improved. These results suggest that the proposed dual dielectric configuration offers a promising approach to overcoming the limited gate voltage range of conventional p-GaN/AlGaN/GaN HFETs, thereby enhancing device reliability.